SISTEM PENUNJANG KEPUTUSAN DIAGNOSA PENYAKIT STROKE DENGAN METODE NAIVE BAYES - Rendy Ramadhiansa (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The purpose of this research is to create an application that is used by the community for diagnosing a stroke on himself by knowing the symptoms experienced and input it into the application. The method used is Naive Bayes method which is calculated based on the probability of the data obtained previously. The data obtained is used into useful information such as systolic blood pressure, blood pressure diastolic, Paralysis door body (tetraparesis, monoparesis, paraparesis and hemiparesis), mouth oblique, loss of speech, loss of taste next to the body, decreased awareness, impaired function of the noble and headaches. The final result of this application is expected to help the general public to make the diagnosis of stroke in order to follow up more quickly if the application diagnose the possibility of having a stroke with an accuracy of 96.58%.